2011
DOI: 10.1089/jpm.2010.0529
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness, Knowledge of Availability, and Readiness for Cancer Palliative Care Services: A Population-Based Survey across Four Regions in Japan

Abstract: Findings show that the public awareness of palliative care services and their availability is insufficient, and cancer-related experiences affect awareness of cancer palliative care but not directly related to typical images for palliative care such as care for patients close to death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 6 publications
3
47
2
Order By: Relevance
“…Consequently, rather than providing an estimation of the extent of public knowledge around palliative care, the value of the findings is in highlighting the sources of that knowledge and those strategies which the participants perceive to be valuable in raising awareness around these issues. These findings contribute to the existing international evidence whilst has demonstrated that public knowledge of palliative care in many societies is limited and that the public is still death-denying [4][5][6][7][8][9][10][11] . The study has found this to be the case in participants with knowledge of healthcare systems and drawn from a membership scheme and it is therefore likely that outside of this group public knowledge of palliative care is much reduced.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consequently, rather than providing an estimation of the extent of public knowledge around palliative care, the value of the findings is in highlighting the sources of that knowledge and those strategies which the participants perceive to be valuable in raising awareness around these issues. These findings contribute to the existing international evidence whilst has demonstrated that public knowledge of palliative care in many societies is limited and that the public is still death-denying [4][5][6][7][8][9][10][11] . The study has found this to be the case in participants with knowledge of healthcare systems and drawn from a membership scheme and it is therefore likely that outside of this group public knowledge of palliative care is much reduced.…”
Section: Discussionmentioning
confidence: 68%
“…2 Public health palliative care or health promoting palliative care is concerned with building public policies that support dying, death, loss and grief, create supportive environments, strengthen community action and allow people to develop personal skills in these area 3 .There are, however, numerous challenges to developing a public health approach, one being the low level of public awareness of palliative care, highlighted by several international surveys. [4][5][6][7] Research continues to suggest that the public is 'death denying' and that conversation about death and dying remains largely 'taboo'. [8][9][10][11][12] Public confusion about end of life terminology is unsurprising when set against the background of debate amongst researchers, practitioners and policy makers about the scope, definitions, goals and approaches of palliative care [13][14] and the changing historical definitions of the term.…”
Section: Introductionmentioning
confidence: 99%
“…However, other quasi‐experimental studies have found that better hospice knowledge may not increase hospice decisions (Selsky et al, ; Sung, Wang, Fan, & Lin, ). Therefore, clarifying the associated factors and constructs is warranted to promote the utilisation of hospices (Hirai et al, ; McIlfatrick et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…41 This was preceded by a survey showing very low levels of awareness. 42 ''Before and after'' surveys over three years showed positive effects on perceptions of the public and bereaved relatives about palliative care over time. Impact on patients' perceptions was less clear.…”
Section: Palliative Care Campaigns S-31mentioning
confidence: 99%